Cation Disorder In Cu2ZnSnS4 Thin Films: Effect On Solar Cell Performances. Issue 9 (16th August 2017) - Malerba, Claudia; Valentini, Matteo; Mittiga, Alberto
Abstract : High (300 °C) and low (160 °C) temperature post deposition annealing treatments are performed on Cu2 ZnSnS4 (CZTS) thin film solar cells to modify the order degree of the CZTS absorber and investigate its effect on the device performances. Large and reversible changes of solar cell parameters are observed, with photovoltaic conversion efficiencies varying from about 4% in the case of more ordered materials, up to nearly 8% after the disordering treatment. Both spectrophotometry and photoluminescence reveal that the ordered materials are characterized by a higher bandgap and a lower deep defect density, whereas the absorption tails and the red shift of the luminescence peak compared to the bandgap are found to be independent of the ordering level. Coherently with the bandgap variation, solar cells in the ordered state are characterized by a lower short circuit current density and a higher open circuit voltage. Ordered devices are found to be limited by low fill factor values, often associated with anomalous "S‐shaped" light J–V curves revealing a blocking behavior. A mechanism based on the increase of a blocking barrier at the CZTS/MoS2 back interface induced by a change in the valence band offset is proposed to explain the lower performances of the ordered devices. Abstract : The effect of cation order degree in Cu2 ZnSnS4 thin films solar cells are investigated . The order degree are varied by different post‐deposition thermal annealing treatments. Measurements on solar cells are combined with optical characterization of the bare absorber to correlate the device performances with the bandgap energy variations and related band alignment changes.